Coordination in clinical managerial practice: Moving things around and making things happen - Meier, Ninna (Scandinavian Journal of Public Administration, 2011)
Considering the vast amounts of resources spent on health care we have surprisingly scarce knowledge of what clinical managers do, when they are at work. Health care organizations are increasingly standardized, and often standardization initiatives and policies point to clinical managers as key figures in implementation processes. Empirical studies of managerial work can give us some indications of parts of clinical managerial practice; we also know that standards are great coordination tools, preferably in stable settings. However, our knowledge of the important relationship between clinical managerial work and standards would benefit greatly from investigations of how clinical managers work with standards in their local, clinical setting. Aspiring to contribute here, this paper compares the relationship between clinical managers’ work and standards across four different hospital units; orthopedic surgery, radiology, stroke and pulmonary medicine. The results show that the relationship between coordination performed by standards and coordination performed by clinical managers vary across the units, depending on level of unpredictability; when unpredictability was high making standards work required more clinical managerial work. Although clinical managerial work faced different challenges in each setting, the coordination practice of clinical managers shared characteristics across all four units.